Intranasal dexmedetomidine sedation for EEG in children with autism spectrum disorder - De Laurentiis, Arianna; Pastori, Chiara; Pinto, Carmela; D’Arrigo, Stefano; Estienne, Margherita; Bulgheroni, Sara; Battaglia, Giulia; Gemma, Marco (Frontiers in Psychiatry, 2024)
The aim of the study was to assess the efficacy of In-Dex sedation in comparison to oral melatonin and hydroxyzine in individuals with Autism Spectrum Disorder (ASD) undergoing EEG recording and determine which categories of patients exhibit the most favorable response to In-Dex sedation.This retrospective observational study involved pediatric patients with ASD who underwent sleep-EEG recording across two periods, before (biennium 2018-19) and after (biennium 2021-22) the routine implementation of In-Dex sedation. Clinical, EEG, and sedation data were stored in a database. A logistic multiple regression model was employed, with the failure of EEG serving as the dependent variable.As concerning results, in this first period 203 EEGs were performed with a rate of failure of 10.8%, while in the second one 177 EEGs were recorded with a percentage of failure of 7.3% (8.3% with MH sedation and 5.8% with In-Dex sedation). No significant adverse events were reported in either period. Multivariate logistic analysis demonstrated that In-Dex decreased the probability of failure (OR=0.25, (0.61-0.88)), while the presence of behavioral disturbances (OR=3.65 ((1.54-8.85)) and the use of antipsychotic drugs (OR=2.76, (1.09-6.95)) increased it.In the light of these results, we can state that In-Dex sedation is safe and reduce EEG failure rate compared to the use of melatonin and hydroxyzine alone, particularly in patients with severe behavioral issues.